What Drives Short-Run Labor Market Volatility in Offshoring Industries? Evidence from Northern Mexico during 2007–2009 - Kaplan, David S.; Lederman, Daniel; Robertson, Raymond (World Bank, Washington, D.C., 2013)
Recent research shows that employment in Mexico's offshoring maquiladora industries is twice as volatile as employment in their U.S. industry counterparts. The analyses in this paper use data from Mexico's social security records and U.S. customs between the first quarter of 2007 and the last quarter of 2009 to identify four channels through which economic shocks emanating from the United States were amplified when transmitted into Mexico's offshoring labor market of Northern Mexico. First, employment and imports within industries are complements, which is consistent with imports being used as inputs for the assembly of exportable goods within industries. That is, when imports fell during the crisis, employment in Mexico was reduced rather than protected by the fall of imports. Second, contrary to other studies, employment is more responsive than wages to trade shocks. Third, fluctuations in Mexico-U.S. trade were associated with changes in the composition of employment, with the skill level of workers rising during downturns and falling during upswings. This implies that the correlation between average wages and trade shocks is partly driven by labor-force compositional effects, which may obscure individual-worker wage flexibility. Fourth, trade shocks affecting related industries (industries linked by employment flows affect employment at least as much as own-industry trade shocks, thus amplifying employment volatility through the propagation of shocks across industries within Northern Mexico. Furthermore, the data suggest that the observed fluctuations in U.S.-Mexico trade at the onset of the Great Recession in the U.S. were not associated with pre-existing employment trends in Northern Mexico.